The effect of goal setting leadership on motivation and work productivity moderated with remote working in the healthcare industry - Putriyah Arifin; Rina Anindita (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2022)
This research was conducted to determine the effect of Goal Setting Leadership on Motivation and Work Productivity moderated by Remote Working. The contribution of this research is expected to add information and provide tangible benefits for the organization and its success in the health care industry so that the objectives to be achieved in this research can be achieved well for the leaders. The analytical tool in this study will use the Structural Equation Model (SEM) and the research was conducted using a survey using a questionnaire via google form distributed in January – May 2021 where the respondents used were 195 employees consisting of non-health employees in the health care industry in Jabodetabek. Data were analyzed using Structural Equation Model (SEM). The results of this study indicate that the first, Good Goal Setting Leadership will increase high motivation, secondly, high motivation will increase good work productivity, thirdly good goal-setting leadership will increase high work productivity. Furthermore, the Remote Working variable as a moderating role on Leadership Goal Setting and Work Productivity will give positive results.